Multiple Glucagon-Producing Pancreatic Neuroendocrine Tumors in a Horse (Equus caballus). (May 2014) - Herbach, N.; Nagel, L.; Zwick, T.; Hermanns, W.
Pancreatic neuroendocrine tumors of glucagon-producing cells are extremely rare in domestic animals. In this report, we describe for the first time, to our knowledge, the incidental finding of multiple glucagon-producing neuroendocrine tumors of the pancreas of a horse. The animal was euthanized due to severe local infection after tooth extraction. On postmortem examination, multiple white nodules of up to 4 cm in diameter were observed in the pancreas. Histologically, pancreatic nodules had the appearance of neuroendocrine neoplasms with positive immunoreactivity for glucagon, synaptophysin, chromogranin A, and neuron-specific enolase. Electron microscopy revealed numerous electron-dense granules, similar to those observed in normal pancreatic alpha cells, in the neoplastic cells. In addition, the left adrenal gland showed multiple hyperplastic foci and adenomas in the medulla that were identified as pheochromocytomas. Based on the morphologic appearance and immunohistochemical staining pattern of pancreatic nodules, a diagnosis of multiple glucagon-producing neuroendocrine tumors was made.